CORPORATE SOCIAL RESPONSIBILITY FOR MICRO, SMALL AND MEDIUM ENTERPRISE (MSME / UMKM) AS A FORM OF ECONOMIC JUSTICE IN BANTEN PROVINCE - Hamdani . (The Management Journal of Binaniaga, 2017)
The purpose of the study is to give an idea relates to the policy of corporate social responsibility (CSR) in actualize economic justice for MSME in Banten Province. This research used descriptive explorative approach by analyzing the empowerment strategies for MSME. The study conducted by using literature review referring on the relevant studies and applicable legislations product including local regulation about CSR. To actualize the economic justice, strategies and policies in supporting the populist economic movement MSME based. The existence of the government is crucial to connect the companies to MSME. The ease of access to funding and business assistance as a strategy to increase the competitiveness MSME in Banten Province. As a commitment to MSME empowerment, the local government could issue the regulation about CSR as a funding sources for MSME. Therefore, the synergic relationship with all parties especially the government, MSME and company need to be developed. The implementation of CSR has been arranged in Perda No 5 of 2016. Technically the used of funding CSR as a source of funding for MSME need to be explained. The goal is that MSME could grow independently. The MSME that grows independently gives people opportunities to work, it means that its existence consistent with the government’s program in addressing the issue of unemployment and poverty. If all parties has the same concern to support the populist economy by using the CSR funding allocation for MSME, the aims of equity and the economic justice for people can be reached.Keywords:  CSR, MSME, and Economic Justice